Correlation analysis of systemic inflammatory response index with erythropoietin hyporesponsiveness and clinical prognosis in maintenance hemodialysis patients - Li Chun-min; Wen Qian; Luo Dan; Wu Jun (Linchuang shenzangbing zazhi)
ObjectiveTo investigate the correlation of systemic inflammatory response index（SIRI） with erythropoietin （EPO） hyporesponsiveness and clinical prognosis in maintenance hemodialysis （MHD） patients.MethodsClinical data of patients undergoing hemodialysis at the Hemodialysis Clinical data of patients undergoing hemodialysis at the Hemodialysis Center of Wuhan Third Hospital between April 1， 2020， and December 31， 2022， were collected and followed up until January 31， 2024. Patients were categorized into high and low ERI groups based on the median of the ESAs resistance index （ERI）. Spearman correlation analysis and logistic regression were applied to analyze the factors influencing EPO hyporesponsiveness. The Kaplan-Meier survival curves and log-rank test were used to compare the survival rates of patients with different SIRI and ERI levels. The relationship between SIRI and poor clinical outcomes in dialysis patients was investigated using Cox regression modeling. The predictive value of SIRI in EPO hyporesponsiveness and death was examined using a receiver operating characteristic （ROC） curve.ResultsA total of 228 patients were included in the study. Percentage of women， percentage of diabetes mellitus， erythrocyte distribution width， platelet count， neutrophil count， and SIRI levels were significantly higher in patients in the higher ERI group （P<0.05）， while the body mass index （BMI）， albumin， pre-dialysis creatinine， dry weight， serum iron， transferrin saturation， hemoglobin， erythrocyte， and intact parathyroid hormone levels were significantly lower （P<0.05）.Multivariate logistic regression analysis revealed that a high SIRI level （>1.56） was an independent risk factor for erythropoietin hyporesponsiveness （OR=2.00， 95%CI： 1.04 to 3.88， P=0.038）. Kaplan-Meier analysis showed that the survival rate for all-cause mortality was significantly lower in the group with higher SIRI levels（all-cause mortality， Log-rank test， χ2=4.1， P=0.043； cardiovascular mortality， Log-rank test， χ2=3.2， P=0.075）. Survival to cardiovascular death was significantly lower in the higher ERI group （all-cause mortality， Log-rank test， χ2=2.9， P=0.087； cardiovascular mortality， Log-rank test， χ2=3.9， P=0.048）. Multivariate Cox regression model analysis showed no significant association between SIRI and the risk of all-cause mortality （HR=1.57， 95%CI： 0.80 to 3.09， P=0.189）.The area under the curve （AUC） of the logistic regression model incorporating SIRI to predict EPO hyporesponsiveness was 0.77 （95%CI： 0.70 to 0.83）， with a sensitivity of 0.754 and a specificity of 0.702. The AUC of SIRI to predict all-cause mortality was 0.68 （95%CI： 0.59 to 0.78）， with an optimal cutoff value of 2.73， a sensitivity of 0.405， and a specificity of 0.919.ConclusionsSIRI is an independent risk factor for EPO hyporesponsiveness， and SIRI and ERI levels are associated with poor clinical outcomes in hemodialysis patients.